Jones, Dan (London, 2006)
2006 "Jones, Dan", 2006, Bishopsgate Institute Dan Jones was a well-known youth and community worker and also the secretary of the Trade Union Council in Tower Hamlets. He struggled for the rights of ordinary Bengali people in and around Brick Lane.